Fast colloidal synthesis of SnSe2 nanosheets for flexible broad-band photodetection. Issue 10 (5th March 2021) - Chen, Guihuan; Zhang, Jinhui; Wang, Hongrui; Yuan, Hua; Sui, Xin; Zhou, Hao; Zhong, Degao
Abstract : A new rapid bottom-up colloidal synthetic route has been developed to synthesize SnSe2 nanosheets within 5 min. A SnSe2 nanosheet-based flexible photodetector is fabricated for the first time and the resulting device displays a wide photodetection range and high flexibility. Abstract : A new rapid bottom-up colloidal synthetic route has been developed to synthesize SnSe2 nanosheets within 5 min. A SnSe2 nanosheet-based flexible photodetector is fabricated for the first time on a polyethylene terephthalate substrate patterned with interdigital Au electrodes. Moreover, the resulting device displays a wide photodetection range (covering 405 to 1064 nm with a photoresponsivity of up to 18.5 mA W −1 ) and high flexibility.